Auditory cognition lab: a music therapy and speech-language pathology co-treatment for military-connected populations with auditory and cognitive impairment - Vetro-Kalseth, Danielle; Vaudreuil, Rebecca; Morrison, Heather; Howland, Kathleen; Bronson, Hannah (Frontiers in Neurology, 2025)
Military personnel are particularly at risk for auditory processing difficulties as their training, occupational, and combat experiences increase the likelihood of long-term damage to the auditory system as well as negatively impact physical, psychological, cognitive, and sensory functioning. This article introduces a music therapy and speech-language pathology co-treatment program, Auditory Cognition Lab (ACL), that treats auditory and cognitive deficits in military-connected populations (service members, veterans) with traumatic brain injury (TBI). ACL addresses auditory discrimination, temporal and binaural processing, and trains compensatory strategies related to auditory processing, cognition, and hearing function. ACL has been clinically implemented at multiple military treatment facilities across the United States. Preliminary outcomes have demonstrated improvement in processing speed, auditory perception, active listening, expressive and receptive language, memory encoding and retrieval, attention at varying levels (sustained, divided, alternating), and self-efficacy. Further research is warranted to learn more about the benefit of this innovative co-treatment program for military-connected individuals with auditory processing deficits and TBI. This paper provides a theoretical framework, comprehensive description and critical reflection of this intervention, and outlines a research strategy for a current feasibility and acceptability study.